2017
DOI: 10.1016/j.jdent.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Open Access: Concepts, findings, and recommendations for stakeholders in dentistry

Abstract: Knowledge about concepts on OA, associated resources and research findings are important for researchers and other users of dental research to make full, appropriate use of OA, and help reduce the avoidable waste caused by inaccessible research. We need more studies into the use and development of OA in dentistry. In addition, joint efforts are required to eliminate the threat of predatory publishing to the dental profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 94 publications
0
9
0
1
Order By: Relevance
“…OA policies (Hua, Shen, Walsh, Glenny, & Worthington, ) were categorised into three types a priori: Direct OA: Journals that were fully OA and without any embargo. Hybrid OA: Journals that were subscription‐based and that offered researchers the option to publish their work as gold OA (gold OA is broadly defined as providing OA articles through journals or publishers) if they paid a specified publication fee “hybrid journals.” Green only: Journals that did not provide an option for gold OA but allowed the authors to make their work OA via self‐archiving (green OA). …”
Section: Methodsmentioning
confidence: 99%
“…OA policies (Hua, Shen, Walsh, Glenny, & Worthington, ) were categorised into three types a priori: Direct OA: Journals that were fully OA and without any embargo. Hybrid OA: Journals that were subscription‐based and that offered researchers the option to publish their work as gold OA (gold OA is broadly defined as providing OA articles through journals or publishers) if they paid a specified publication fee “hybrid journals.” Green only: Journals that did not provide an option for gold OA but allowed the authors to make their work OA via self‐archiving (green OA). …”
Section: Methodsmentioning
confidence: 99%
“…Hua et al [ 18 ] published a narrative review specific to OA concepts in dentistry in which they go beyond OACA and venture into other topics such as research waste of inaccessible research. Regarding OACA, they looked at nine studies across many disciplines and found variation of methods and materials, but ultimately the citation advantage ranged from -5% to 83% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al [ 18 ] published a narrative review specific to OA concepts in dentistry in which they go beyond OACA and venture into other topics such as research waste of inaccessible research. Regarding OACA, they looked at nine studies across many disciplines and found variation of methods and materials, but ultimately the citation advantage ranged from -5% to 83% [ 18 ]. Turk [ 19 ] published an overview on OA, pertaining only to medical articles, looking at OA factors in which studies of possible OACA mostly found a citation advantage, but articles reporting randomized controlled trial (RCT) results revealed no OACA.…”
Section: Introductionmentioning
confidence: 99%
“…For the author, publication in an open-access journal means that their work is 90% more likely to be read and 42% more likely to be downloaded as a PDF in the six months following publication than a comparable subscription-access article in the same journal [2]. The precise impact of open access publishing on citation rates is still debated [3]. For example, in a recent cohort study of 5835 medical journals, open access journals had a significantly higher CiteScore, percent cited, and source normalized impact per paper, but the non-open access journals had a higher scholarly output [4].…”
Section: Advantages Of the Open Access Publishing Model In Medicinementioning
confidence: 99%